Is Public Agricultural Expenditure Effective on Agricultural Production in Sub-Saharan Africa? - CHABOSSOU, AUGUSTIN FOSTER COMLAN; POUAKONE SECHOUTDI, Yaya (My University, 2020)
This study examines the nexus between government agricultural expenditure and agricultural production in SSA while using panel data from 33 SSA countries from 2001 to 2018. Data are from several sources that is FAOSTAT, ASTI and IFPRI, and the empirical evidence is based on a system Generalized Method of Moments from Blundell and Bond (1998). This method controls for unobserved heterogeneity, potential endogeneity of the explanatory variables and correlated individual effects. Empirical findings reveal that government agricultural expenditure has a positive and significant relationship with agricultural production both in the short run as well in the long run. This study recommends that government should adhere to the Maputo Declaration by allocating at least 10% of their budgets to the agriculture sector for a higher agricultural production, to increase the level of socio-economic infrastructures so as to incite farmers to increase their production and finally to facilitate the attribution of land titles.
Keywords: Government agricultural expenditure; System GMM; SSA; Agriculture; Production